1994
DOI: 10.1093/ajcn/60.6.930
|View full text |Cite
|
Sign up to set email alerts
|

Premature infants require additional folate and vitamin B-12 to reduce the severity of the anemia of prematurity

Abstract: One hundred eighty-four premature infants, < 1800 g at birth and < 36 wk gestation, were entered into a study investigating the role of additional folate and vitamin B-12 supplementation of the anemia of prematurity. All patients initially received vitamin E and iron in accordance with accepted standards. Patients were randomly assigned to four groups to receive orally 0.1 mg folate/d for 4 mo, 100 micrograms vitamin B-12 intramuscularly monthly for 4 mo, both supplements, or neither. All other activities incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 17 publications
1
18
0
1
Order By: Relevance
“…Sick preterm infants are thought to be at risk of developing low Se levels during early life due to the small Se stores resulting from the short gestation period and from the lim ited dietary intake of Se [1,[3][4][5][6]9]. Previous observations [3][4][5][6]9] showed that blood Se indices fall progressively after birth in pre term infants, unless their diet is supple mented with Se.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sick preterm infants are thought to be at risk of developing low Se levels during early life due to the small Se stores resulting from the short gestation period and from the lim ited dietary intake of Se [1,[3][4][5][6]9]. Previous observations [3][4][5][6]9] showed that blood Se indices fall progressively after birth in pre term infants, unless their diet is supple mented with Se.…”
Section: Discussionmentioning
confidence: 99%
“…Previous observations [3][4][5][6]9] showed that blood Se indices fall progressively after birth in pre term infants, unless their diet is supple mented with Se. The postnatal change in uri nary Se in our preterm infants was strikingly different from that of the term infants.…”
Section: Discussionmentioning
confidence: 99%
“…at 6 weeks was associated with a normal cobalamin status at 4 months (median serum cobalamin 420 pmol/L; median plasma tHcy 4.57 µmol/L) (Bjorke- Monsen et al 2008). This dose represents approximately twice the RDA of cobalamin for the first year of life (Table 1) and has been associated with increased hemoglobin levels (Worthingtonwhite et al 1994) and reduced tHcy and MMA levels in premature infants (Bjørke- Monsen et al, unpublished observations 2003). In severe cobalamin deficiency, different regimes have been proposed (Rasmussen et al 2001).…”
Section: Treatmentmentioning
confidence: 99%
“…Des apports de folates (100 μg/kg par jour) et vitamine B12 (100 μg/kg par mois) sans Epo augmentent l'érythro-poïèse chez le nouveau-né prématuré [39].…”
Section: Risques Associés à L'utilisation De L'epo De Synthèse En Néounclassified